Abnormal nociceptive processing occurs centrally and not peripherally in pain-free Parkinson disease patients: A study with laser-evoked potentials. (January 2017) - Zambito-Marsala, Sandro; Erro, Roberto; Bacchin, Ruggero; Fornasier, Annalisa; Fabris, Federico; Lo Cascio, Cecilia; Ferracci, Franco; Morgante, Francesca; Tinazzi, Michele
Abstract: Background: Several studies documented abnormal nociceptive processing in PD patients. Pain central pathways are accessible by laser-evoked potentials (LEPs). LEPs recording show a N2/P2 complex mostly generated by the anterior cingulate cortex, preceded by an earlier negative component (N1), originating from the opercular cortex. Previous work demonstrated N2/P2 amplitude reduction in PD patients and suggested a centrally-acting pathomechanism for the genesis of pain. However, since a peripheral deafferentation has been recently demonstrated in PD, it is not clear if such LEP abnormalities reflect a mechanism acting centrally or not. Objective: To assess whether abnormalities of nociceptive inputs occur at central and/or peripheral level in pain-free PD patients with hemiparkinson using Nd:YAP LEPs. Methods: We recorded scalp Nd:YAP-LEPs to hand stimulation in 13 pain-free patients with unilateral PD and in 13 healthy subjects. Additionally, we collected laser pain-rating in both groups. Results: PD patients and normal subjects showed comparable N1, N2 and P2 latencies. The N2/P2 amplitude was significantly lower in PD patients than in controls, regardless of the clinically affected side, whereas the N1/P1 amplitude was not different. PD patients had higher pain-rating, indicative of hyperalgesia. Conclusions: These findings demonstrate that in the PD patients the abnormal processing of pain stimuli occurs at central rather than peripheral level. The co-existence of hyperalgesia and reduced amplitude of the N2/P2 complex, in spite of a normal N1/P1 component, suggests an imbalance between the medial and lateral pain systems. Such a dissociation might explain the genesis of central pain in PD. Highlights: Pain is a common symptoms in PD that is often unrelated to the motor disturbances. We observed a significantly reduced N2/P2 LEPs component on both sides, while the N1/P1 component was normal. PD patients had higher laser pain rating than controls, indicative of hyperalgesia. An imbalance between the medial and lateral pain system might explain the genesis of central pain and hyperalgesic phenomena.